The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1002/(sici)1521-4109(199807)10:9<647::aid-elan647>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Aniline-Bonded Catechols in Aqueous Solution and Their Electrochemical Behavior at a Carbon Felt Electrode

Abstract: The oxidized form of catechol (1,2-benzoquinone) reacts with aniline at neutral pH range and the electroactive 1:1 and 1:2 compounds of catechol and aniline which exhibit separative reversible redox waves are produced and their formal electrode potentials are ¹0.05 V and ¹0.23 V, respectively. The 1:1 compound is considered to be an adduct with pink color and the 1:2 compound is considered to be two anilines substituted catechol from the MS data of molecular weight (290) and 1 H and 13 C NMR data. The 1:2 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The strong presence of both signals indicate near complete oxidation of the initial mixed dimer (quinone-diamine Michael addition product) to the final repeating unit as shown in Scheme . These findings are consistent with similar reports in the literature. , …”
Section: Resultssupporting
confidence: 94%
“…The strong presence of both signals indicate near complete oxidation of the initial mixed dimer (quinone-diamine Michael addition product) to the final repeating unit as shown in Scheme . These findings are consistent with similar reports in the literature. , …”
Section: Resultssupporting
confidence: 94%
“…Moreover, in this case, new small redox waves ͑IIa and IIc͒ appeared during a potential scan, and these redox waves remained even after the electrode was washed. As described earlier, 9 the oxidized form of catechol ͑1.2-benzoquinone͒ reacts with aniline, and anilinebonded catechol compounds show reversible or quasi-reversible redox waves. The redox waves of the adduct of amino group and 1,2-benzoquinone are observed at about −0.1 V vs Ag/AgCl, and the amino group-substituted catechol exhibits redox waves at about +0.05 V vs Ag/AgCl.…”
Section: Resultsmentioning
confidence: 80%
“…It has been reported that the oxidized form of catechol ͑1,2-benzoquinone͒ reacts with amine compounds such as aniline and dialkylamines, 8 and the redox waves of the adduct of 1,2-benzoquinone and aniline and those of the aniline-substituted catechol were reported in our previous paper. 9 If an amino group is introduced to a graphite carbon surface, an aniline-like structure may be formed. Then, similar redox waves of aniline-bonded catechol can be expected to appear when the cyclic voltammetry using a pre-electrolyzed electrode is carried out in an ammonium carbamate solution.…”
mentioning
confidence: 99%